Dari Sekolah Ke Dunia Kerja: Strategi Siswa Smk Menghadapi Tantangan Era Digital Dan Teknologi Informasi - EE Lailatul Putri; Muhammad Maulana Yusuf; Mohammad Jibril; Daffa Raihan Thoriq; Nabila Reva Zalianti; Jasmine Putri Sugianto (KAMI MENGABDI, 2026)
The development of digital technology has significantly transformed workforce competency requirements, demanding that Vocational High School (SMK) graduates possess skills relevant to the modern workplace. However, there remains a gap between the competencies of vocational students and industry needs, particularly in terms of digital literacy, soft skills, and understanding of future job trends. This Community Service Program aimed to enhance the understanding and readiness of vocational high school students in facing the challenges of the digital workforce era. The activity was conducted on May 6, 2026, at SMKN 54 Jakarta, involving students of Class X TKJ 2 as participants. The implementation method employed an educational and participatory approach through interactive lectures, discussions, and question-and-answer sessions. The materials delivered covered developments in the digital workplace, industry-required competencies, digital literacy, soft skills development, and personal branding strategies. The results of the activity indicated an improvement in participants’ understanding of the challenges and opportunities in the digital workforce, increased awareness of the importance of developing both hard skills and soft skills, and greater motivation to prepare for their careers from an early stage. The program successfully achieved its objectives and strengthened collaboration between higher education institutions, particularly the Informatics Study Program, and schools in developing competent and adaptive human resources.